Experiential Avoidance and Non-Suicidal Self-Injury - Haywood, Sophie Brandy (Curtin University, 2023)
My thesis explores the role of experiential avoidance in self-injury. It is comprised of four studies. Overall, I found support for experiential avoidance but rather than a unidimensional construct we need to view experiential avoidance as a multidimensional construct and use language reflective of the lived experience.